Gegen eine rückwärtsgewandte Wirtschaftspolitik — unbequeme Wahrheiten mit hoher Halbwertszeit - Christoph M. Schmidt (Wirtschaftsdienst, 2025)
– In 2013, the German Council of Economic Experts advised the then future German government to pursue a decisively marketoriented economic reform agenda in the fields of labour market and pension policy, tax policy and climate policy. Yet, policy makers have ignored this advice, basically disregarding the foreseeable demographic transformation. Meanwhile, new additional challenges have emerged, which require a seriously revitalised German economy. Thus, the next German government should shift to a marketoriented course in its economic policy, particularly by unleashing entrepreneurial motivation.
Keywords: D72; H11; H50; 330; Wirtschaftspolitik; Deutschland; Wirtschaftspolitik; Deutschland